Teaching Strategies to Apply in the Use of Technological Tools in Technical Education - Olga Arranz García; Vidal Alonso Secades (Multidisciplinary Journal for Education, Social and Technological Sciences, 2014)
The emergence of new technologies in education area is changing the way of organizing the educational processes. Teachers are not unrelated to these changes and must employ new strategies to adapt their teaching methods to the new circumstances. One of these adaptations is framed in the virtual learning, where the learning management systems have been revealed as a very effective means within the learning process. In this paper we try to provide teachers in engineering schools how to use in an appropriate way the different technological tools that are present in a virtual platform. Thus, in the experimental framework we show the results outcomes in the analysis of two data samples obtained before and after the implementation of the European Higher Education Area, that would be extrapolated for its innovative application to the learning techniques.